2017
DOI: 10.3892/etm.2017.5601
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapeutic effects of high intensity focused ultrasound and Metformin for the treatment of adenomyosis

Abstract: Abstract. Adenomyosis is a pathological gynaecological condition characterized by benign invasion of the endometrium into the myometrium. High intensity focused ultrasound (HIFU) is one of the most common therapeutic strategies for the treatment of adenomyosis. However, the efficacy of single HIFU therapy is insufficient for the treatment of patients with adenomyosis. In the present study, the efficacy of HIFU and metformin for the treatment of adenomyosis was analyzed in 274 patients with adenomyosis who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This ATP detection assay is currently the most sensitive and has minimal interferences [24]. While FUS treatment induced a significant reduction of viable cells in both tumour spheroids over time with plate reader estimation, specialised techniques of spatial-temporal quantification [25] might bring more relevant data. The significant reduction of the spheroid area in U87 spheroids is congruent with the significant loss in cellular ATP metabolism showing the collapse of U87 cells.…”
Section: Discussionmentioning
confidence: 99%
“…This ATP detection assay is currently the most sensitive and has minimal interferences [24]. While FUS treatment induced a significant reduction of viable cells in both tumour spheroids over time with plate reader estimation, specialised techniques of spatial-temporal quantification [25] might bring more relevant data. The significant reduction of the spheroid area in U87 spheroids is congruent with the significant loss in cellular ATP metabolism showing the collapse of U87 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study indicated that combined HIFU and metformin treatment have a superior effect in patients with enlarged adenomyosis compared with single HIFU treatment, even though HIFU monotherapy could significantly reduce menstrual flow and pain [47]. Another report by Guo Y et al [44] revealed that combination therapy of GnRHa and HIFU could also improve the short-term clinical efficacy of HIFU ablation.…”
Section: Discussionmentioning
confidence: 99%
“…The findings demonstrated that follow-up inflammatory cytokine concentration (interleukin-1, 6, and 8), cancer antigen 125, menstrual volume, and pain of HIFU plus metformin group were significantly better than those of single HIFU group, suggesting that combined HIFU and metformin treatment is more efficient than single HIFU ablation. 23…”
Section: Sizementioning
confidence: 99%